The Model of a System for Criteria-Based Assessing of Students’ Functional Literacy and its Developmental Impact - Sagimbaeva, Ainur Ye.; Avdarsol, Sailaugul; Zaslavskaya, Olga Yu.; Arynova, Gulnar S.; Baimakhanova, Aigerim S. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Objective: The purpose of this article is to compile a model of a system for assessing students’ functional literacy based on a criteria-based approach. Background: Everyone use a traditional five-point grading system to assess students’ activities, but using it, it’s not always possible to objectively evaluate student work. Therefore, the authors use the criteria-based student assessment system in our lessons. Method: Criteria based assessment involves a mechanism that allows evaluating students more objectively. Assessing the activities of students in the lesson becomes democratic, since a student is the subject of his training, and a teacher does not play the role of a “judge” in grading. Results: As a result of the study, it was revealed that the assessment system makes it possible to determine how successfully one or another educational material is mastered, or a certain practical skill is formed. At the same time, it is advisable to take a mandatory minimum as a reference point. Conclusion: The criteria-based assessment system is completely transparent in the sense of how to give formative and summative grades, as well as the goals for which these grades are put. It is also a means of diagnosing learning problems, providing and ensuring constant contact between a teacher, student, and parents. Based on the conducted practical experiment, the effectiveness of the model of the system for assessing the functional literacy of students based on the criteria-based approach in computer science has been proved.